The unintended consequences of school-based health and nutrition policies: a systematic review - Turner, Samantha L.; Libert, Alexis M.; Haase, Grace; Pan, Zhaoyi; Austin, Andrew; Timko, C. Alix (Frontiers in Psychology, 2024)
Background Significant funding and attention are directed toward school-based health and nutrition interventions. Less attention is given to the potential unintended consequences of these policies, especially those that target children and adolescents. This systematic review aimed to elucidate the unintended consequences of school-based health and nutrition policies in the United States. Methods We conducted a systematic review, adhering to PRISMA guidelines, to analyze quantitative, qualitative, and mixed methods research conducted between January 2013 and September 2023. The search strategy encompassed three databases, identifying 11 articles that met the inclusion criteria. Results Unintended consequences were organized into four themes: disordered weight control behaviors, parental discomfort or encouragement of disordered weight control behaviors, eating disorder triggers, and financial losses. The analysis of disordered weight control behaviors indicates limited impact on youth, and we noted limited consensus in the assessment of these behaviors. We observed parent concerns about BMI screening and reporting as well as apprehensions about privacy and efficacy. There were fewer articles addressing eating disorder antecedents, although there was evidence that some youths with eating disorders considered school health class a trigger of their disorder. One study was identified that found an increase in food waste following replacement of sugar-sweetened beverages. Implications Findings underscore the importance of comprehensive evaluation and consideration of unintended consequences in the development and implementation of school-based health policies. Recommendations include further longitudinal research, integrating obesity prevention with eating disorder prevention, and de-implementation when unintended consequences potentially outweigh benefits, such as in BMI screening and surveillance. Systematic Review Registration: Identifier CRD42023467355. https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=467355